2022
DOI: 10.1002/ehf2.13976
|View full text |Cite
|
Sign up to set email alerts
|

Experience with the potassium binder patiromer in hyperkalaemia management in heart failure patients in real life

Abstract: Aims Hyperkalaemia (HK) is common in heart failure (HF) patients, related to renal dysfunction and medical treatment. It limits medical therapy optimization, which impacts prognosis. New potassium (K) binders help control HK, allowing better medical management of HF. Methods and results A retrospective multicentre register included all outpatients with HF and HK (K ≥ 5.1 mEq/L) treated with patiromer according to current recommendations. We evaluated analytic and clinical parameters before starting the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Current guidelines highlight the role of PBs in managing HK and preventing its recurrence ( McDonagh et al, 2021 ; Heidenreich et al, 2022 ). Newer PBs may also permit the continuation or intensification of RAASi therapy ( Agarwal et al, 2021 ; Imamura et al, 2021 ; Montagnani et al, 2021 ; Williams et al, 2021 ; Esteban-Fernández et al, 2022 ), which will improve the outcome of HF patients, as suggested by the ESC guidelines ( McDonagh et al, 2021 ). However, at the time of this study, the PBs available in Japan were SPS and CPS.…”
Section: Discussionmentioning
confidence: 99%
“…Current guidelines highlight the role of PBs in managing HK and preventing its recurrence ( McDonagh et al, 2021 ; Heidenreich et al, 2022 ). Newer PBs may also permit the continuation or intensification of RAASi therapy ( Agarwal et al, 2021 ; Imamura et al, 2021 ; Montagnani et al, 2021 ; Williams et al, 2021 ; Esteban-Fernández et al, 2022 ), which will improve the outcome of HF patients, as suggested by the ESC guidelines ( McDonagh et al, 2021 ). However, at the time of this study, the PBs available in Japan were SPS and CPS.…”
Section: Discussionmentioning
confidence: 99%